An overview of akhlak and moral concepts and their relevance to Moral Education in Malaysia - S De Asildo, Noor Zulina; Yasin, Maizura; Abdullah, Nur Surayyah Madhubala; Mokhtar, Marzni Mohamed (Macrothink Institute, 2022)
Moral Education (ME) in Malaysian context is closely related to “akhlak” and moral concept. The use of the terms “akhlak” and moral in achieving the goal of forming people with noble character through the subject of ME has been influenced by Islam as the official religion of Malaysia and the diversity of religious beliefs in the Malaysian community. Moral Education is a complex subject in Malaysia, not only because it is studied by non-Muslim students of various religious beliefs, but also because it may probably be taught by Muslim teachers. Based on a review of theories and previous researches, this paper will discuss the basic principles of "akhlak" and moral and their relationship with the formation of people with noble characters through the ME subject in Malaysia. This paper contributes to the possibility of aligning “akhlak” and moral concepts in order to achieve the goal of forming people with noble characters through the ME subject. Hence, this paper expands on existing literature to better understand the complexities underlying ME subject due to the diversity of religious beliefs among ME teachers and students.